Experimental and numerical study of the effects of nozzle taper angle on spray characteristics of GDI multi-hole injectors at cold condition. (1st September 2020) - Wu, Shengqi; Gandhi, Anand; Li, Hongjiang; Meinhart, Mark
Highlights: Spray characteristics of GDI injectors with different nozzle taper angles were studied. Nozzle taper angle of GDI injectors has no obvious effect on nozzle static flow rate. Nozzles with larger taper angles generated shorter and wider fuel spray. Nozzles with larger taper angles resulted in smaller fuel drops. Abstract: With today's stringent legislative requirements, every combustion/emission contributing component must be researched and optimized in modern gasoline direct injection (GDI) engines. However, a limited amount of research on the taper angle of gasoline injector nozzles can be found. In this study, three GDI fuel injectors are investigated to study the effects of nozzle taper angle on spray characteristics. All of the injectors have the same inlet diameter, and the only difference is the nozzle taper angle. Fuel pressure was set at 200 bar and fuel temperature was at room temperature. A numerical method was used to study the internal nozzle flow, and various optical techniques were applied to investigate the spray characteristics. It was found that adjusting the nozzle taper angle didn't induce any noticeable difference in the static flow rate, which was linear with the square root of the pressure differential across the orifice plate. As a result, the initial tip penetration was proportional to the injection timing, and nearly independent with the nozzle taper angle. For well-developed sprays, larger nozzle taper angle resulted in shorter penetration and faster breakup. Increasing the nozzle taper angle resulted in larger space between internal flow and the nozzle wall, which enhanced air entrainment into the nozzle. Consequently, flow radial velocity at the nozzle exit increased, which was beneficial to spray breakup and atomization. Larger nozzle taper angle resulted in wider fuel plume, larger plume angle, broader and shorter global spray, which increased the possibility of plume interaction. Smaller fuel drops were measured from the injectors with larger taper angle. Finally, it shows that adjusting the taper angle of the nozzle offers an additional degree of freedom when trying to optimize the spray characteristics of an injector for improved fuel atomization, engine combustion performance and emissions reduction.